Outwitting the devil : the secret to freedom and success - Hill, Napoleon, 1883-1970.; Lechter, Sharon L. (New York : Sterling, 2011)
Originally written in 1938 but never published due to its controversial nature, an insightful guide reveals the seven principles of good that will allow anyone to triumph over the obstacles that must be faced in reaching personal goals.
My first meeting with Andrew Carnegie -- A new world is revealed to me -- A strange interview with the devil -- Drifting with the devil -- The confession continues -- Hypnotic rhythm -- Seeds of fear -- Definiteness of purpose -- Education and religion -- Self -discipline -- Learning from adversity -- Environment, time, harmony, and caution.
Includes index.
Keywords: Success -- Psychological aspects; Success; New Thought; Success -- Psychological aspects